2009
DOI: 10.1021/je800770s
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Characterization of Materials for Phase-Change Memory Cells

Abstract: The thermal properties of the phase-change chalcogenide alloy Ge2Sb2Te5 in its three phases (amorphous, cubic, and hexagonal) and of Si3N4 and SiO2 have been studied to obtain reliable values for device modeling. Thermal conductivity was determined, along with a quantitative estimation of the thermal resistances of the layers’ interfaces, not negligible for highly scaled devices. Electrical resistivity of the chalcogenide material has also been investigated during the phase transition by in situ measurement at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 17 publications
6
28
1
Order By: Relevance
“…The acoustic properties of the crystalline phases are very similar, and the difference in the thermal conductivity is attributed to the electron contribution, which is also in good agreement with predictions using the Wiedemann-Franz law and separate measurements of electrical properties [116,128]. Heat conduction across interfaces with surrounding passivation and electrode materials (SiO 2 [121,123], ZnS:SiO2 [114], TiN [125,128,130], Al [129]) is governed by acoustic properties and interfacial disorder [125,130].…”
Section: Phase Change Memoriessupporting
confidence: 75%
See 2 more Smart Citations
“…The acoustic properties of the crystalline phases are very similar, and the difference in the thermal conductivity is attributed to the electron contribution, which is also in good agreement with predictions using the Wiedemann-Franz law and separate measurements of electrical properties [116,128]. Heat conduction across interfaces with surrounding passivation and electrode materials (SiO 2 [121,123], ZnS:SiO2 [114], TiN [125,128,130], Al [129]) is governed by acoustic properties and interfacial disorder [125,130].…”
Section: Phase Change Memoriessupporting
confidence: 75%
“…The PCM research community has leveraged and extended the TDTR and 3ω methodologies to reveal a variety of the fascinating thermal transport phenomena that occur in the phase-change chalcogenides [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130]. The TDTR methodology has proven useful for extracting coupled (and even decoupling [125]) film and interface properties.…”
Section: Phase Change Memoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermal cross-talks among the different bits is a crucial reliability issue in PCM. Although experimental data on thermal conductivity are available for few materials in this class, [6][7][8] it is unclear whether the value measured in the bulk phase could also describe the behavior of the material in nanoscaled devices (10-20 nm) which might be smaller than the phonon mean free path. This is particularly relevant for PCM architectures based on nanostructures employing nanowires, 9 colloidal nanoparticles, 10 thin bridges, 11 and nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…8 The electrical resistivity varies over several decades, according to the phase: in the amorphous state GST is an insulator ͑up to 1 ⍀ m͒, whereas in the crystalline state, it becomes conductive ͑10 −4 -10 −3 ⍀ m for the fcc crystalline and about 10 −5 ⍀ m for the hcp crystalline͒. 9 Previous work 10 has shown that the thermal conductivity of GST does not exhibit such a large variation during the phase change transformation. Nevertheless, even if the variation remains small, the thermal conductivity is a sensitive parameter when simulating the heat transfer in a memory device based on such a phase change material.…”
Section: Introductionmentioning
confidence: 99%